Identifikasi Penyakit Jantung Menggunakan Machine Learning: Studi Komparatif - sintiya, endah septa; Rizdania, Rizdania; Afrah, Ashri Shabrina (Jurnal Transformatika, 2024)
Heart disease is the number one cause of death globally. This condition is followed by an unhealthy lifestyle. Heart disease prediction needs to be done considering the importance of health. The presence of machine learning has made it easier for humans to make early detection of patterns approaching heart disease. This study compares 6 machine learning methods for disease classification with KNN, Naïve Bayes, Decision tree, Random forest, logistic regression, and SVM. The final classification obtained ranking accuracy with the highest value in the KNN method with precision, accuracy, re-call, fi-score tests. It is hoped that these results can be applied to real case studies of heart disease.